Soybean phosphorus-use efficiency in the moist Savanna of West Africa - Ogoke, I.; Togun, A.; Dashiell, Kenton E. (Informa UK Limited, 2006)
With limited access to P fertilizers, soybean (Glycine max (L.) Merr.) varieties cultivated in the moist savanna zone of West Africa should use P as efficiently as possible. Field trials were conducted on the effect of P application on grain yield per unit P accumulated (physiological efficiency or PPE), amount of P accumulated in plant biomass per unit P applied in fertilizer (recovery efficiency or PRE), and the amount of grain produced per unit of applied P (yield efficiency or PYE) in soybean. There was greater proportional root proliferation at lower P rates, and at sites where soil test P was low. Physiological efficiency was higher under these conditions. Although a greater proportion of total dry weight was accumulated in the roots of the early and medium (27-28%) compared with the late varieties (22-23%), root dry weight and PPE in the latter were higher. At maturity, PPE was significantly reduced from 245 kg kg−1 with no P applied to an average of 173 kg kg−1 (or by about 29%) with P application. Phosphorus yield efficiency was higher at sites (Kasuwan Magani and Gidan Waya) and in the late varieties where response to P was highest. PYE with 60 kg ha−1 P applied rate was almost half the value observed with 30 kg P ha−1.